Global food prices, local weather and migration in Sub-Saharan Africa - Lars Ludolph; Barbora Sedova (ZBW - Leibniz Information Centre for Economics, 2021)
In this paper, we study the effect of exogenous global crop price changes on migration from agricultural and non-agricultural households in Sub-Saharan Africa. We show that, similar to the effect of positive local weather shocks, the effect of a locally-relevant global crop price increase on household out-migration depends on the initial household wealth. Higher international producer prices relax the budget constraint of poor agricultural households and facilitate migration at an order of magnitude of around one third of the net effect of positive local weather shocks. Unlike positive weather shocks, which mostly facilitate internal rural-urban migration, positive income shocks through rising producer prices only increase migration to neighboring African countries, likely due to the simultaneous decrease in real income in nearby urban areas. Finally, we show that while higher producer prices induce conflict, conflict does not play a role for the household decision to send a member as a labor migrant.
Keywords: O15; O55; Q56; Q54; 330; labour migration; food prices; climate; Africa